2009
DOI: 10.1063/1.3152602
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen atoms in Debye plasma environments

Abstract: Plasma-screening effects are investigated on hydrogen atoms embedded in weakly coupled plasmas. In the present context, bound state wave functions are introduced related to the screening Coulomb potential ͑Debye model͒ using the Ritz variation method. The bound energies are derived from an energy equation, which contains one unknown variational parameter. To calculate the parameter numerically, fixed-point iteration scheme is used. The calculated energy eigenvalues for various Debye lengths agree well with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 44 publications
4
28
0
2
Order By: Relevance
“…Its accuracy has been checked in earlier calculations. 17,18,21,89 It has been found that the eigen energies corresponding to this wave function are very close to the corresponding most accurate eigen energies computed by using the Slater-type orbital 90…”
Section: Resultsmentioning
confidence: 59%
“…Its accuracy has been checked in earlier calculations. 17,18,21,89 It has been found that the eigen energies corresponding to this wave function are very close to the corresponding most accurate eigen energies computed by using the Slater-type orbital 90…”
Section: Resultsmentioning
confidence: 59%
“…-Energy level shifts of ions in dense plasmas have been found experimentally and theoretically for many decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The reason for this phenomenon is related to the fact that the plasma shields the nuclear attraction of the bound electron that in turn shifts the energy level toward the continuum.…”
Section: Copyright C Epla 2012mentioning
confidence: 99%
“…However, in the strongly coupled plasma (Γ ≫ 1 implying high density and low temperature) ion-sphere (IS) potential model [4] is the best suited model for accounting the plasma screening effects. Both the Debye and ion-sphere models have been successfully employed sev-eral times earlier to describe the electronic properties of different plasma embedded atomic systems [5][6][7][8][9][10][11]. The effect of nuclear charge screening by plasma free electrons is reciprocated in form of ionization potential depression (IPD) or continuum lowering [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%